Glomerular nodules and long-spacing collagen in kidneys of patients with multiple myeloma. Issue 10 (October 1974) - Schubert, G. E.; Adam, A.
Abstract : Light microscopic examination of the kidneys in 170 patients with multiple myeloma revealed three from patients without diabetes with glomerular nodules that were indistinguishable from those of diabetic glomerular sclerosis. Electron microscopic studies showed the nodules to be deposits of fine-grained material that corresponded to precipitations of protein but lacked the basement-membrane-like material characteristic of nodular glomerulosclerosis in diabetics. What is more, a unique collagen was observed in the marginal area of the nodules and in the periglomerular interstitium. The possible causes of the origin and distribution of this collagen not so far described in the human kidney are discussed.